2017
DOI: 10.1021/acs.jpclett.7b00200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of an Excited-State Triplet Species upon Photoactivation of the Chlorophyll Precursor Protochlorophyllide

Abstract: The chlorophyll precursor protochlorophyllide (Pchlide), which is the substrate for the light-driven enzyme protochlorophyllide oxidoreductase, has unique excited-state properties that facilitate photocatalysis. Previous time-resolved spectroscopy measurements have implied that a long-lived triplet state is formed during the excited-state relaxation of Pchlide, although direct evidence of its existence is still lacking. Here we use time-resolved electron paramagnetic resonance (EPR) in combination with time-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Steady-state absorption spectra were taken using a PerkinElmer lambda-1050 spectrometer. A previously reported 19 Ti:sapphire amplifier system (Spectra Physics Solstice Ace) was used to generate 800 nm pulses at 1 kHz for the TA experiments. A portion of this beam was used to pump an optical parametric amplifier (Topas Prime) with an associated NIR−UV−vis unit to achieve the 100 fs pump pulses at 350 nm with a beam diameter of 360 μm.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Steady-state absorption spectra were taken using a PerkinElmer lambda-1050 spectrometer. A previously reported 19 Ti:sapphire amplifier system (Spectra Physics Solstice Ace) was used to generate 800 nm pulses at 1 kHz for the TA experiments. A portion of this beam was used to pump an optical parametric amplifier (Topas Prime) with an associated NIR−UV−vis unit to achieve the 100 fs pump pulses at 350 nm with a beam diameter of 360 μm.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…For the transient absorption (TA) experiments, a Ti:sapphire amplifier system (Spectra Physics Solstice Ace) was used to generate 800 nm pulses at 1 kHz, as previously reported. 22 A portion of this beam was used to pump an optical parametric amplifier (OPA) (Topas Prime) with an associated NIR−UV−vis unit to achieve the pump pulses at 420, 450, and 480 nm (∼10 nm full width at half-maximum, 100 fs, 250 nJ). The rest of the OPA output was passed through a sapphire crystal to generate a white light continuum, which was used as the probe to record changes in absorption between 435 and 720 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[85][86][87][88][89][90][91] This process is highly dependent on solvent polarity 85,86,90 and is attributed to a number of polar groups attached to Pchlide, including an electron-withdrawing carbonyl group on ring E. 91 The excited state of Pchlide is quenched through solvation of this intramolecular charge-transfer species, [85][86][87][88][89][90][91] and a triplet state is then formed on the nanosecond timescale with a quantum yield of approximately 30 %. [89][90][91][92] Excited state charge separation across Pchlide has also been confirmed computationally, and these calculations suggest that this leads to site-specific solvation of photoexcited Pchlide through strengthening of H-bonding interactions. 91,93 Photochemical studies of the mechanism in the ternary enzyme-substrate complex are challenging 74,76 but it appears that the dipolar character of excited state Pchlide is also important in LPOR photocatalysis (Figure 4).…”
Section: Determinants Of Photocatalysis Identified From Enzyme Structuresmentioning
confidence: 73%
“…Timeresolved spectroscopy has been used to investigate these excited state properties, and studies have shown that Pchlide is highly reactive. [85][86][87][88][89][90][91][92] Excitation brings about charge separation across Pchlide. [85][86][87][88][89][90][91] This process is highly dependent on solvent polarity 85,86,90 and is attributed to a number of polar groups attached to Pchlide, including an electron-withdrawing carbonyl group on ring E. 91 The excited state of Pchlide is quenched through solvation of this intramolecular charge-transfer species, [85][86][87][88][89][90][91] and a triplet state is then formed on the nanosecond timescale with a quantum yield of approximately 30 %.…”
Section: Determinants Of Photocatalysis Identified From Enzyme Structuresmentioning
confidence: 99%